2019
DOI: 10.1126/sciadv.aat5778
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free, highly selective synthesis of ammonia from nitrogen and water by a plasma electrolytic system

Abstract: Lightning in a bottle: Plasma enables selective, electrolytic production of ammonia from nitrogen and water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
226
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(229 citation statements)
references
References 36 publications
0
226
1
2
Order By: Relevance
“…An example is that of degradable plastics produced by targeted bond engineering and photoinduced “click chemistry.” These materials may lead to a new generation of plastic materials that pose no contamination hazard to our planet. As mentioned earlier, better use of renewable (e.g., solar and wind) energy for microplasma generation, and scaling the discharges by employing integrated electrode arrays may be a promising approach to developing zero‐emissions energy conversion systems that are readily transported and operated off‐the‐grid. A potential impact of integrating with renewable energy is the possibility of sustainably converting cheap feedstocks such as CO 2 , water, and N 2 to value‐added chemicals …”
Section: Discussionmentioning
confidence: 99%
“…An example is that of degradable plastics produced by targeted bond engineering and photoinduced “click chemistry.” These materials may lead to a new generation of plastic materials that pose no contamination hazard to our planet. As mentioned earlier, better use of renewable (e.g., solar and wind) energy for microplasma generation, and scaling the discharges by employing integrated electrode arrays may be a promising approach to developing zero‐emissions energy conversion systems that are readily transported and operated off‐the‐grid. A potential impact of integrating with renewable energy is the possibility of sustainably converting cheap feedstocks such as CO 2 , water, and N 2 to value‐added chemicals …”
Section: Discussionmentioning
confidence: 99%
“…15 More recently, Hawtof and co-workers were able to demonstrate the formation of ammonia in water, showing that electrons can indeed cross the plasma-liquid interface in a discharge plasma. 16 We have shown that helium plasma at atmospheric pressure in the absence of hydrogen was effective at reducing copper oxide films, suggesting that electrons alone are, in the case of copper, sufficient for the reduction process. 17 This view is supported by Lee et al 18 and Sui et al 19 who loaded metal ions in a polymer matrix and showed using an APPJ that the reduction of the metal ions was indeed driven by plasma (or secondary) electrons.…”
Section: Introductionmentioning
confidence: 87%
“…Ryan Hawtof et al. reported a hybrid electrolytic system of a gaseous plasma electrode without any material surface (Figure b) and the FE for NH 3 can be achieved to 100 % from N 2 and H 2 O at ambient temperature and pressure …”
Section: Are the Individual Steps And The Overall Process Of Electrocmentioning
confidence: 99%